Acoustic Voice Quality Index and Acoustic Breathiness Index as two examples for strengths and weaknesses of free software in medicine. (May 2020) - Stappenbeck, Lydia; Barsties v. Latoszek, Ben; Janotte, Ben; Lehnert, Bernhard
Abstract: Objective: The purpose of the study was to explore the extent to which different Praat versions affect the reproducibility of results performing Acoustic Voice Quality Index (AVQI) and Acoustic Breathiness Index (ABI). Method: Seven Praat versions were selected and categorized into three groups based on hierarchical cluster analysis. The differences/distances, diagnostic accuracy, and concurrent validity were evaluated among the three groups. Group three had just one Praat version. This version was found after two month to have a computation bug in smoothed cepstral peak prominence (i.e., an important measure for AVQI and ABI) before a new update removed this bug. For the analyses, a previous database of 218 German voice samples and auditory-perceptual judgment results were used. Results: The AVQI and ABI results between group 1 and 2 (p = 0.53, and p = 0.62, respectively) demonstrated no significant differences. However, the results between these two groups and group 3 yielded significant differences for AVQI and ABI (all p < 0.00001). The concurrent validity for AVQI (r = 0.84 to 0.86) and ABI (r = 0.84 to 0.85) were strong in all three groups. The diagnostic accuracy of both indices was also sufficient for group one and two but low in group three particularly in sensitivity (AVQI: 23% and ABI: 9%, respectively). Conclusion: AVQI and ABI are two robust measurements in the evaluation of voice quality. However, caution is warranted using updates in open source software such as Praat for patient care or research.